ANALISIS MINAT BELAJAR PESERTA DIDIK DENGAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) - Dias Ayu Larasati; Sutirna Sutirna; Indrie Noor Aini (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The aims of this research is to know the improvement of students’ interest mathematic with teams games tournament (TGT) learning model. The background of this research is the lowest of students’ interesting in learning mathematic on SMP Islam Al- Mu’min. the research used quasi experiment methode and descriptive quantitative technique. The population of this research is all the students of eight grade on SMP Islam Al-Mu’min, while the sample is student of eight A. The instrument that used in this research is non-test instrument named quitionnare.   The quitionnaire is about the students interest after they learn used TGT model with 11 questions. The result of this research is the percentage of student’s interest is positive with the value is 76,62% in each indicator. It’s mean most of the student have interest in learning mathematics with TGT.